2016
DOI: 10.1159/000441293
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis of Nail Apparatus Melanoma: 20 Years of Experience from a Single Institute

Abstract: Introduction and Objectives: Nail apparatus melanoma (NAM) is an uncommon tumor, especially in Caucasians. The prognosis of patients affected by NAM was analyzed and correlated with the histopathological criteria and the surgical management of the tumors. Materials and Methods: We collected data regarding NAM referred to the Skin Cancer Unit of the Dermatology Department of the University of Bologna, from 1992 to January 2012. Results: Out of 1,327 melanoma cases diagnosed between 1992 and 2012, 42 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 24 publications
3
41
1
4
Order By: Relevance
“…Patients’ data were recorded, including age, sex, location (involved finger), width of the pigmented band (categorized as less than 1/3 of the nail plate, between 1/3 and 2/3 of the nail and more than 2/3), presence or absence of nail dystrophy and Breslow thickness (for nail apparatus melanoma). The evaluated dermoscopic variables are analytically described (see Table ) and are based on literature data . Finally, the presence of granular pigmentation defined as fine light to dark brown granularity, was included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients’ data were recorded, including age, sex, location (involved finger), width of the pigmented band (categorized as less than 1/3 of the nail plate, between 1/3 and 2/3 of the nail and more than 2/3), presence or absence of nail dystrophy and Breslow thickness (for nail apparatus melanoma). The evaluated dermoscopic variables are analytically described (see Table ) and are based on literature data . Finally, the presence of granular pigmentation defined as fine light to dark brown granularity, was included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluated dermoscopic variables are analytically described (see Table 1) and are based on literature data. 3,6,9,10 Finally, the presence of granular pigmentation defined as fine light to dark brown granularity, was included in the analysis.…”
Section: Analysis Of Dermoscopic Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study confirms other reports in the literature that concluded that the surgical approach does not affect the prognosis of nail melanoma. [3][4][5] Although the literature shows that histologic characteristics such as tumor thickness, 4,5 presence of mitosis, and To the Editor: With recent increases in incidence rates of melanoma and nonmelanoma skin cancer (NMSC), especially in young people, skin cancer is important in survivorship research. Risk of multiple skin cancers may be associated with ultraviolet (UV) radiationerelated behaviors after a sentinel skin cancer.…”
mentioning
confidence: 99%
“…45 In our experience, the conservative approach with functional surgery 46 involving the excision of the whole NU is a good option for the treatment of non-invasive NUM (MIS, Ia staging). 47,48…”
Section: Onychomatricomamentioning
confidence: 99%